2020
DOI: 10.1074/jbc.ra119.012213
|View full text |Cite
|
Sign up to set email alerts
|

High cell density increases glioblastoma cell viability under glucose deprivation via degradation of the cystine/glutamate transporter xCT (SLC7A11)

Abstract: The cystine/glutamate transporter system xc− consists of the light-chain subunit xCT (SLC7A11) and the heavy-chain subunit CD98 (4F2hc or SLC3A2) and exchanges extracellular cystine for intracellular glutamate at the plasma membrane. The imported cystine is reduced to cysteine and used for synthesis of GSH, one of the most important antioxidants in cancer cells. Because cancer cells have increased levels of reactive oxygen species, xCT, responsible for cystine–glutamate exchange, is overexpressed in many cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 58 publications
1
27
1
Order By: Relevance
“…Consequently, glucose starvation significantly limits NADPH supply in KEAP1 -deficient cancer cells, despite that these cells express high levels of NADPH-generating enzymes and reductases; combining glucose starvation with high cystine uptake in KEAP1 -deficient lung cancer cells leads to NADPH depletion, drastic accumulation of disulfide molecules (including GSSG, γ-glutamylcystine, and glutathionylcysteine), and ultimately cell death. While previous studies showed that glucose starvation induces massive accumulation of intracellular cystine (as well as these other disulfides mentioned above) in SLC7A11 high cancer cells (which are non-lung cancer cells and do not harbor KEAP1 mutation) ( Liu et al., 2020b ; Yamaguchi et al., 2020 ), surprisingly, in this study, we found that glucose starvation does not induce obvious cystine accumulation in KEAP1 -KO H1299 cells. The lack of cystine accumulation in this cell line is particularly striking given that glucose starvation actually increases cystine uptake in these cells ( Figure 2 B).…”
Section: Discussioncontrasting
confidence: 75%
“…Consequently, glucose starvation significantly limits NADPH supply in KEAP1 -deficient cancer cells, despite that these cells express high levels of NADPH-generating enzymes and reductases; combining glucose starvation with high cystine uptake in KEAP1 -deficient lung cancer cells leads to NADPH depletion, drastic accumulation of disulfide molecules (including GSSG, γ-glutamylcystine, and glutathionylcysteine), and ultimately cell death. While previous studies showed that glucose starvation induces massive accumulation of intracellular cystine (as well as these other disulfides mentioned above) in SLC7A11 high cancer cells (which are non-lung cancer cells and do not harbor KEAP1 mutation) ( Liu et al., 2020b ; Yamaguchi et al., 2020 ), surprisingly, in this study, we found that glucose starvation does not induce obvious cystine accumulation in KEAP1 -KO H1299 cells. The lack of cystine accumulation in this cell line is particularly striking given that glucose starvation actually increases cystine uptake in these cells ( Figure 2 B).…”
Section: Discussioncontrasting
confidence: 75%
“…SLC7A11 and SLC3A2 are two subunits of system X C − . Despite SLC7A11 is predominantly important for the function of system X C − [27,28], growing evidences have demonstrated that SLC3A2 is equally important for preventing cells from over lipid peroxidation [29,30]. Additionally, SLC3A2 is also required for erastin to induce ferroptosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency of glutamate, cysteine, and glycine affects the expression level of GSH in cells. However, intracellular Cystine concentration is regulated by cystine-glutamate transporter system (X c − ), which consists of two subunits (light chain xCT and heavy chain 4F2hc), on the cell membrane (Liu L. et al, 2020;Yamaguchi et al, 2020). xCT is the cystine/glutamate antiporter solute carrier family 7 member 11 (SLC7A11) that enhances cystine uptake and GSH biosynthesis, thereby inhibiting oxidative stress and iron death (Liu L. et al, 2020).…”
Section: Regulation Of Ferroptosis By Cysteine-glutathione (Cys-gsh) mentioning
confidence: 99%